Empyema caused by Eikenella halliae diagnosed by metagenomic next-generation sequencing (mNGS) after pulmonary surgery: A case report - Huang, Jie; Wang, Liming; Xu, Yumei; Hu, Xinhua; Yu, Ronghuan; Chen, Shi; Wang, Baoqing (Frontiers in Public Health, 2022)
Background: Empyema is one of the complications of pulmonary surgery for lung cancer, the incidence of which is not very high, but in severe cases it can even lead to death, and it is always difficult to diagnose the cause by conventional methods. Case Presentation: Here, we report a clinical case of empyema caused by Eikenella halliae after a pulmonary surgery in a 55-year-old man. He had a fever, cough, and expectoration for three days, and was diagnosed with right hydropneumothorax and empyema, pneumonia, postoperative malignant tumor of the right lower lobe (adenocarcinoma) and hypertension. The microbiology laboratory reported Gram-negative bacteria in pleural effusion, which was preliminarily considered as Eikenella based on culture and 16S rRNA sequencing. Furthermore, metagenomic next-generation sequencing (mNGS) of sputum samples was performed twice, and reported negative result and E. halliae, respectively. The pathogen was finally confirmed as E. halliae by whole genome sequencing, suggesting the high resolution ability of mNGS in the clinical diagnosis of this case. Conclusion: To our knowledge, this is the first case report of E. halliae infection in China, indicating increased pathogenicity of Eikenella sp. in immunocompromised patients, especially after invasive operations. Our findings emphasize that mNGS allows bacterial diagnosis of lung abscess and can significantly improve the accuracy of the diagnosis.